Synergistic effects of potassium humate and clay-rich soil on improving the chemical and physical properties of tin tailing - Panghingguan, Lambang Praja; Hartono, Arief; Syaiful, Anwar (Journal of Degraded and Mining Lands Management, 2026)
West Bangka Regency, Bangka Belitung Islands Province, is one of Indonesia's main tin-producing areas. Mining activities in this area produce residues in the form of tailings that dominate the post-mining landscape. Tailings are a sand-textured medium with low water retention, unstable aggregate structure, and limited nutrient content. This condition hinders the use of land for ecological reclamation purposes. This experiment examined the effect of the combination of potassium humate and clay-rich soil on improving the quality of tin tailings. The method of experiment was an incubation method, and it was designed in a Completely Randomized Design with two factors. The factors were potassium humate and clay-rich soil.  The rates of potassium humate were 0% 0.50%, 1.00%, 1.50% while the rates of clay-rich soil were 0%, 5.00%, 10.0%, 20.0%. The parameters analyzed were organic Carbon (C), Cation Exchange Capacity (CEC), Water Holding Capacity (WHC), and soil pH.  The results showed that the combination of 1.50 % potassium humate and 20% clay-rich soil was the best treatment for increasing organic C content to 1.50% and CEC to 7.27 cmol(+)/kg. This treatment also increased the WHC to the level 18.8 %. As for soil pH, the treatment of 1.50% potassium humate without the application of clay-rich soil had the highest value, with a value of 8.02.  These findings proved that the integration of potassium humate and clay-rich soils significantly improved the chemical and physical characteristics of tin tailings, thereby increasing their feasibility as a sustainable reclamation medium.